1998
DOI: 10.1007/bf03347278
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive in vivo bioassay detects bioactive human growth hormone in transduced primary human keratinocytes

Abstract: An improved in vivo body weight gain bioassay for the potency determination of human growth hormone (hGH) has been set up in "little" mice (lit/lit), a mutant derived from the C57BL/6J strain. This improved assay now has a detection limit of the order of 0.05 micrograms/mouse/day, which corresponds to a sensitivity about 20-fold higher than that of the most sensitive in vivo assay reported up to now: the tibia test in hypophysectomized rats or mice. This sensitivity was achieved mainly by introduction of a car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…The increases in body weight were preceded in both groups by a considerable decrease in weight on day 2. It is of interest that in a previous study, in which mice received three subcutaneous injections per day of hGH-conditioned culture medium (equivalent to 0.16 µg hGH/day), a similar decrease in weight was observed also on the second day after treatment (18). In that study, however, the slope of the weight variation curve for the test group was about fourfold lower than that in the present experiment, whereas the slope of the control group was essentially zero.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…The increases in body weight were preceded in both groups by a considerable decrease in weight on day 2. It is of interest that in a previous study, in which mice received three subcutaneous injections per day of hGH-conditioned culture medium (equivalent to 0.16 µg hGH/day), a similar decrease in weight was observed also on the second day after treatment (18). In that study, however, the slope of the weight variation curve for the test group was about fourfold lower than that in the present experiment, whereas the slope of the control group was essentially zero.…”
Section: Resultsmentioning
confidence: 72%
“…As established in previous studies (18,26), two daily injections of 5 µg hGH to "little" mice lead to an average weight increase of 0.195 ± 0.010 g/animal/day (n=5, 10-day assays); this corresponds to an increase in the initial weight of ~15%. Figure 4 shows the hGH levels over a 24 h period in the circulation of "little" mice receiving two injections of 5 µg hGH.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Grafted mice also showed an increase in body weight (0.060 g/animal/day), which was significantly higher (P<0.01) than that of the controls (0.023 g/animal/day). This was the first time that continuous in vivo secretion of the hormone and subsequent phenotypic alterations due to the grafting of transduced, hGH-secreting primary human keratinocytes had been demonstrated in lit/scid mice, an animal model known to be very sensitive to low concentrations of hGH 13 . Conventional epidermal sheets of these mGH-secreting keratinocytes, prepared by us using the classical technique of Barrandon et al 2 , showed a drop in secretion rates of >80% simply due to detachment of the epithelium from its substratum.…”
Section: Ex Vivo Strategiesmentioning
confidence: 97%
“…• Ao final do experimento de longa duração (6 • Os órgãos do grupo tratado com DNA plasmidial que apresentaram as maiores • Os níveis de mIGF-I do grupo tratado com DNA plasmidial foram significativamente superiores em relação ao grupo salina, após 1 (P<0,01), 2 (P<0,001), 3 (P<0,001), 5 (P<0,01) e 6 (P<0,001) meses de tratamento.…”
Section: Conclusãounclassified